2019
DOI: 10.1111/nhs.12654
|View full text |Cite
|
Sign up to set email alerts
|

Training needs analysis of Korean nurses' neurological assessment competency

Abstract: Despite the importance of neurological assessment, there is a lack of research directed at nurses' competency in performing these assessments. We aimed to identify nurses' competency levels in performing neurological assessments and prioritize their related training needs using importance–performance analysis. This survey research was conducted and reported based on the enhancing the quality and transparency of health research (EQUATOR) guidelines. A total of 213 nurses participated in a descriptive, cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Liu and Lin defined competence as follows: knowledge, skills, abilities, traits, or motivation directly related to work performance or other important achievements in life, which is the decisive factor for individuals to take successful actions in work or situations [5]. Bae and Roh define it as follows: the potential characteristics of individuals that can lead to excellent performance at work, including motivation, characteristics, knowledge, skills, selfimage, or social roles [6][7][8]. Makarov defines it as a potential and deep-seated personal feature that distinguishes the excellent from the mediocre in a job.…”
Section: Related Workmentioning
confidence: 99%
“…Liu and Lin defined competence as follows: knowledge, skills, abilities, traits, or motivation directly related to work performance or other important achievements in life, which is the decisive factor for individuals to take successful actions in work or situations [5]. Bae and Roh define it as follows: the potential characteristics of individuals that can lead to excellent performance at work, including motivation, characteristics, knowledge, skills, selfimage, or social roles [6][7][8]. Makarov defines it as a potential and deep-seated personal feature that distinguishes the excellent from the mediocre in a job.…”
Section: Related Workmentioning
confidence: 99%
“…Traumatic Brain Injury (TBI) is the disruption of normal brain function due to external injuries caused by blunt head trauma, accident, suddenly bumps to the head, violent hitting of the head or other causes that damage the skull and injured the brain tissues (Bae & Roh, 2020). TBI is a leading cause of death and disability worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Sound knowledge and e cient skill performance of nurses may helpful to deal with complexities of neurological assessment of unconscious patients with traumatic brain injuries (TBI) (Greenshields, 2019). E cient nursing assessment found associated with early patients recovery in neuro and general surgery departments (Bae & Roh, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Efficient nursing assessment was found associated with early patients recovery in neurosurgery and general surgery departments. 7 A study reported that nurses, working in neurosurgery department have poor knowledge and practices about GCS assessment of TBI patients. About 40% of all patients who admit in hospitals with traumatic brain injuries, rather to recover, their conditions get more worsen due to improper assessment and poor management.…”
Section: Introduction Introductionmentioning
confidence: 99%